Novel drug delivery system: a promising approach in management of schizophrenia â A review - Moin, Shaikh Gulam; Sharma, Neha; Rane, Meenal (Journal of Applied Pharmaceutical Research, 2017)
Schizophrenia is a syndromic condition which is characterized by a set of signs and symptoms like delusions. It is severe non-curable illness of the brain. If not controlled and treated properly, it can lead to severe consequences. One can control these delusions by means of treatment, by using Conventional therapy or Novel therapy. There are various advantages of Novel system over Conventional system. This review focuses on understanding Novel system and its advantages over Conventional system.